Breast cancer racial differences before age 40--implications for screening. - Johnson, Edwin T. (National Medical Association, 2002)
BACKGROUND: Most authorities advocate mammogram screening for breast cancer beginning at age 40 based on the age-specific distribution and incidence of breast cancer in the general population. This policy has been bolstered by studies that demonstrate that, for the general population, mammography in the 40-49 age bracket reduces mortality. However, it also has been reported that African-American breast cancer patients are diagnosed more often than white patients below the age of 40. Young African-American women are also more likely to have advanced disease at the time of diagnosis with predictably higher mortality. The purpose of this investigation is to explore the question, whether a subset of African-American women, age 30-39, by virtue of increased vulnerability, would benefit from early mammogram screening. STUDY DESIGN: The age-specific distribution (age 30-84) of African-American and white breast cancer patients in five State cancer registries were compared. Prognostic indicators (tumor size and nodal status) in two of the five registries in African-American and white breast cancer cases below the age of 40 were compared. Age-specific incidence in the 30-39 age group and the relative populations of black and white women in the United States were noted in the Surveillance Epidemiology and End Report (SEER) (1994-1998) and The U.S. Census 2000. RESULTS: The differences of age-specific distribution and age-specific incidence of African-American and white breast cancer patients were found to be significant. More than 10% of African-American women with breast cancer were diagnosed before age 40 compared to 5% of white patients. The incidence of breast cancer (SEER Report 1994-1998) in the 30-39-age bracket for African-American and white women was 48.9 and 40.2 at the 95% confidence level, while the proportion of African-American and white women reported by the Census Bureau was not too dissimilar, 15.8% and 14.6% respectively. Prognostic indicators (tumor size and nodal status) support the notion that young African-American women are more likely to have advanced disease at diagnosis. CONCLUSIONS: African-American women in the 30-39 age group have twice the age-specific distribution, have a higher incidence compared to their white counterparts, and exhibit more ominous prognostic signs. This study provides evidence that African-American women in the 30-39 age category represent a high-risk group that may benefit from efforts at earlier detection. Although mammography remains the preferred screening modality, investigators have pointed out difficulties encountered when using mammography in young women, including low sensitivity, high breast density, cost/benefit concerns, and low positive predictive value. Nevertheless, the increasing mortality and persistent racial incidence gap in young African-American women, age 30-39, argue for considering early screening mammography in spite of recognized concerns.